Rhetorical Structure in Indonesian Research Article Introductions Using Loi’s Framework - Rahman, Yenni Arif; Fitriyeni, Fitriyeni; Apriyanti, Fitri; Habibah, Fiza Asri Fauziah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
This study explores the rhetorical structure of Indonesian research article (RA) introductions by examining how they align with or diverge from Swales’ Create-A-Research-Space (CARS) model, as interpreted through Loi’s contrastive rhetoric framework. Using a qualitative genre analysis of 30 RA introductions from SINTA tier 1-3 Indonesian journals in linguistics and education, published between 2022-2024, the research identifies the presence and realization of the three CARS moves. Findings show that while Move 1 (establishing a territory) and Move 3 (occupying the niche) appear in all texts, and Move 2 (establishing a niche) in most, their rhetorical realization diverges from conventional Anglophone patterns. Indonesian authors tend to expand Move 1 with philosophical or policy-based narratives, express Move 2 indirectly without explicit critique, and delay or repeat Move 3 in a recursive fashion. These patterns reveal dominant cultural-rhetorical strategies such as indirectness, collective voice, and contextual elaboration. The findings underscore the influence of local discourse traditions on academic writing and call for more culturally responsive genre models in English for Academic Purposes (EAP) pedagogy.